2022
DOI: 10.1097/pcc.0000000000002932
|View full text |Cite
|
Sign up to set email alerts
|

Health Resource Use in Survivors of Pediatric Septic Shock in the United States

Abstract: To evaluate postdischarge health resource use in pediatric survivors of septic shock and determine patient and hospitalization factors associated with health resource use. DESIGN:Secondary analyses of a multicenter prospective observational cohort study. SETTING:Twelve academic PICUs. PATIENTS:Children greater than or equal to 1 month and less than 18 years old hospitalized for community-acquired septic shock who survived to 1 year. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS:For 308/338 patients (91%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Lastly, health resource use such as hospitalizations and ED visits are additional measures to evaluate long-term outcomes and, as demonstrated in this cohort and other critically ill pediatric cohorts, are frequent occurrences and likely to be highly disruptive to recovery or evidence of ongoing impairments (2, 37, 38). Furthermore, this study highlights that nearly half of patients required therapy support after discharge, further supporting the involvement of these specialists during the acute illness.…”
Section: Discussionmentioning
confidence: 88%
“…Lastly, health resource use such as hospitalizations and ED visits are additional measures to evaluate long-term outcomes and, as demonstrated in this cohort and other critically ill pediatric cohorts, are frequent occurrences and likely to be highly disruptive to recovery or evidence of ongoing impairments (2, 37, 38). Furthermore, this study highlights that nearly half of patients required therapy support after discharge, further supporting the involvement of these specialists during the acute illness.…”
Section: Discussionmentioning
confidence: 88%
“…In Australia and New Zealand (ANZ), our most contemporary data, [2006][2007][2008][2009][2010][2011][2012][2013][2014][2015][2016], indicate that about one-in-six children with septic shock admitted to the PICUs die (3). Moreover, survivors frequently suffer serious sequelae, which affect long-term health-related quality of life (4). Most children with septic shock present with rapid deterioration, and in our ANZ 2012-2015 experience, half of the deaths occurred within 48 hours of presentation (5).…”
mentioning
confidence: 99%
“…Furthermore, this association persists after adjustment for acute organ dysfunction and length of hospitalization, suggesting that comorbidity development, specifically chronic respiratory failure and supplemental nutritional dependence, is not merely a reflection of severity of acute illness but is more specific to sepsis. Although prior studies have shown increased rates of health care use, hospital readmission, and new medical device dependence after sepsis (and therefore hinted at the development and progression of comorbid conditions as a driver of these outcomes), this study assessed directly for new or progressive comorbid conditions …”
Section: Discussionmentioning
confidence: 99%